Comparing remote and in-person interpretation experiences for clinicians and Spanish-speaking patients with limited English proficiency: a mixed methods study - Hector P Rodriguez; Timothy T Brown; Jacob Chen; Xiaoyu Cai; Alondra Ruiz; Paola Hernandez Fernandez (BMJ Open Quality)
Objective There is concern that remote medical interpretation is not as patient-centred as in-person interpretation, but limited evidence exists comparing interpreter service delivery methods. Using mixed methods, remote and in-person professional medical interpretation were examined from the perspectives of Spanish-speaking patients with limited English proficiency and community health centre (CHC) clinicians.Design Patient experience survey data from Spanish-speaking patients and interviews of primary care clinicians assessed their experiences of using remote versus in-person interpretation. Multivariable regression models estimated the association of the interpreter method with patient-reported experiences of (1) clinician communication and (2) interpreter support.Setting Three CHC organisations in California, USA.Intervention Remote versus in-person medical interpretation.Primary outcomes Patients’ and clinicians’ experiences of using in-person versus remote professional medical interpretation.Results We recruited 303 Spanish-speaking patients (mean age: 40.4, % female: 69.0%) to complete a survey assessing their experiences with professional medical interpretation and 19 clinicians who used professional medical interpretation for interviews. In regression analyses of patient experience survey data, no evidence of an association between the interpreter method used and patient-reported experiences of clinician communication or interpreter support was found. In interviews, however, clinicians strongly preferred in-person interpreters and highlighted operational and communication challenges associated with using remote interpreters. Interviews revealed six themes related to interpreter services delivery methods: (1) in-person interpretation supports effective communication and clinician-patient relationships, (2) in-person interpretation enhances operational efficiency, (3) cost-effectiveness of delivery methods depends on language demand and clinic needs, (4) in-person interpretation enhances quality control and reduces privacy risks, (5) considerations when integrating external personnel and (6) the availability of and limited use of audio-video medical interpretation.Conclusions To meet the operational needs of CHCs, policymakers and healthcare payers should consider expanding payment models that enable the provision of interpreter services using multiple methods.